ICARE LEARNING STRATEGY TO IMPROVE THE WRITING ABILITY OF THE STUDENTS AT FISHERY AGRIBUSINES DEPARTMENT - Dedi Setiawan; Amaluddin; Latifa, Ammang (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2021)
The aim of this research was to find out the impact of the implementation of ICARElearning steps in improving the students’ writing ability at fishery agribusiness department of SMKN 7 Pinrang. This research applied quasi experimental design with non equivalent control group design. The total number of sample were 59 students in which class X AP1 consist of 29 students and class X AP2 consist of 30 students. The instrument used in this research was writing descriptive teks. The data was collected through pre-test and post test. The result of the data analysis showed that the writing ability of the students improved. Despite the students’ writing ability in control class also improve, but the improvement is not as significant as in experimental class. Therefore, the result of this research showed that ICARE learning strategy can be an alternative way to solve the problem in the classroom, especially for writing skills.